Synergism between essential oils: A promising alternative to control Sitophilus zeamais (Coleoptera: Curculionidae) - Santana, Alisson da Silva [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Santos, Thais Lohaine Braga dos [UNESP]; Baptista, Yago Alves [UNESP]; Santos, Maria Clezia dos [UNESP]; Lima, Ana Paula Santana [UNESP]; Tanajura, Lívia Stenico; Vieira, Tatiana Manzini; Crotti, Antônio Eduardo Miller (Elsevier, 2022)
Combinations of essential oils (EOs) are promising alternatives for pest management in storage grains. A high diversity of compounds in EOs and EO mixtures can increase their toxicity. Additionally, EOs can be useful in insecticide resistance programs. For this reason, we evaluated the fumigant toxicity and repellent effects of six essential oils (Dysphania ambrosioides, DA; Pelargonium graveolens, PE; Piper arboreum, PA; Piper diospyrifolium, PD; Piper gaudichaudianum, PG; and Piper tuberculatum, PT) separately and in binary combinations against adults of Sitophilus zeamais (the maize weevil). First, the insecticidal activity of all possible combinations of the six EOs were assessed. Next, the concentrations needed to cause 50% and 90% mortality (LC50 and LC90, respectively) in the S. zeamais population were determined for the most toxic EOs and mixtures. After that, the synergistic effect of the mixtures was also verified. Finally, the most toxic treatments were assessed to determine the time required to cause mortality of 50% of the population and check the repellent effects on S. zeamais. The binary mixtures of DA and PE, PT, PG, PD, and PA were the most toxic against S. zeamais. The LC50 and LC90 values for these treatments ranged between 1.77 and 2.25 μL L−1 and from 2.42 to 7.64 μL L−1, respectively. The mixtures were more toxic than the EOs tested separately, which indicates the occurrence of synergistic effects. All treatments caused mortality of 50% of the population of S. zeamais in less than 42 h of exposure. In addition, the combinations DA + PE, DA + PT, DA + PG, and DA + PA were repellent to S. zeamais. Based on these results, we conclude that the mixtures of EOs evaluated in this study are highly promising for the control of S. zeamais populations and can also be used for resistance management of this species.
Keywords: Binary mixtures; Dysphania ambrosiodes; Essential oils; fumigation; Maize weevil; Repellency